Efficiency analysis and derivation of enhanced deployment models for sensor networks. (23rd February 2012) - Oldewurtel, Frank; Mähönen;, Petri
In this paper we analyse the efficiency of Distributed Source Coding (DSC) and its dependence on the node deployment strategies for Wireless Sensor Networks (WSN). The impact of correlation in both node locations and sensed phenomenon on the performance of WSNs in realistic environments is investigated. We show that significant energy savings and lifetime extensions are possible using DSC under different deployment models and varying data correlation structures. Furthermore, we derive enhanced pseudo–random deployment models that exploit different amounts of a priori information. Those models lead to significantly optimised initial network deployments which can be subsequently used with other existing optimisation techniques. The derived comprehensive framework enables thorough and realistic evaluation of WSNs even on bit–level. Overall the energy–efficiency, sensing coverage and lifetime of WSNs are strongly improved by our suggested deployment strategy.